A plan for a national hospital service
1946-03-18 1946 1940s 2 pages A PLAN FOR A NATIONAL HOSPITAL SERVICE prepared by THE BRITISH HOSPITALS ASSOCIATION The establishment of a National Health Service is not in itself a matter of politics; but is entirely a matter of how to provide the patient with the best possible service. The following plan for a National Service, within a National Health Service, is prompted solely by the desire that the patient shall be assured of the best possible service. This plan provides on a secure financial basis a comprehensive service free to the citizen, combining the resources of the State with all that is best in the existing services, including the voluntary hospitals with their pioneering spirit, tradition and experience. This plan maintains a balance between the organisation required for a National Service on the one hand and the obvious dangers in any national plan on the other hand — loss of the personal and human touch, loss of local interest and the danger of making the patient fit the scheme instead of the scheme being made to fit the patient. It provides for the voluntary hospitals to be retained alongside Local Authority (or State) hospitals, but working together, as has already been done in some parts of the country, in a service properly planned and organised over Regions and centrally directed on a national basis. It acknowledges that the success of the voluntary hospitals has been chiefly due to their methods of direct management and to the widespread personal interest which they have attracted to their work. It leaves the individual hospital the necessary freedom to endeavour to improve its own service and retains local interest. In the long run, the patient will judge the national service not on the merits of its organisation as a whole, but on the actual service which he receives from the individual hospital. THE HOSPITALS' PLAN 1. The Minister of Health would assume general responsibility for the direction and financing of the hospital service required within the National Health Service. 2. A Central Hospitals Board would be appointed by the Minister to which, subject to his veto, he would delegate the major duties and responsibilities, including the framing of national policy. This Board would be wholly or largely representative in its composition of the major agencies through which alone the Minister can design and operate the service, i.e., the medical profession, voluntary hospitals, the local authorities, the dentists, nurses and pharmacists. The Minister would therefore appoint the Board after consultation with the appropriate bodies. 292/842/2/65